Concordance and Discordance between Radiology Resident’s and Radiologist’s Interpretation of Brain MRI in Patients with Head Masses: Brain MRI in Patients with Head Masses - Anwar, Khadeeja; Safi, Abdullah; Abid, Hadia; Khan, Irfanullah; Anwar, Umar; Anwar, Talha; Sundal, Anisa (Pakistan Journal of Health Sciences, 2023)
Diagnosis of head masses involves clinical examination, neurological signs, and radiological imaging. MRI is the preferred imaging tool for detailed assessment of tumor, its extent and treatment plan. Objective: To find the level of concordance and discordance between radiology resident’s and consultant’s interpretation of MRI (Magnetic Resonance Imaging) done for brain masses. Methods: A cross sectional study was conducted at the radiology department of Rehman Medical Institute, Peshawar. Simple random sampling was done and sample size was calculated using kappa coefficients (Donner and Rotondi) n=100. 100 patients who visited department of Radiology over a period of two years were assessed by prospective analysis of their radiology reports. Senior resident’s and consultant’s reports were compared. All pre-op patients were included irrespective of age or gender. Data were collected and recorded on a specially designed proforma and entered into Microsoft excel and analyzed using SPSS (Version 22.0. IBM Corp., Armonk, NY). Results: MRI brain reports of 58 male and 42 female patients were evaluated. The most common tumors were gliomas, making up 52% of the total tumors. Metastasis being second most common tumor making 16%, meningiomas in 15%, pituitary tumors in 10% and vestibular schwannomas in 7% of the patients. Concordance, discordance, and Cohen’s Kappa values in different masses were gliomas. (Concordance=88.46%, Discordance=11.54%, k=0.336), Meningiomas (Concordance=86.66%, Discordance=13.34%, k=0.423), Metastasis (Concordance=81.25%, Discordance=18.75%, k=0.294), Pituitary Tumors (Concordance=80%) Discordance=20%, k=0.375) and Vestibular Schwannomas (Concordance=85.71%, Discordance= 14.29% k=0.588). Conclusions: There was no statistically significant difference between senior resident’s and consultant radiologist’s report of MRI brain masses.